Generation of effective and specific human TCRs against tumor/testis antigen NY-ESO-1 in mice with humanized T cell recognition system - Chen, Xiaojing Tina; Leisegang, Matthias; Gavvovidis, Ioannis; Pollack, Seth M.; Lorenz, Felix K. M.; Schumacher, Ton N.; Daumke, Oliver; Blankenstein, Thomas (Frontiers in Immunology, 2024)
Generation of high avidity T cell receptors (TCRs) reactive to tumor-associated antigens (TAA) is impaired by tolerance mechanisms, which is an obstacle to effective T cell therapies for cancer treatment. NY-ESO-1, a human cancer-testis antigen, represents an attractive target for such therapies due to its broad expression in different cancer types and the restricted expression in normal tissues. Utilizing transgenic mice with a diverse human TCR repertoire, we isolated effective TCRs against NY-ESO-1157-165 restricted to HLA-A*02:01. We compared the functions of the murine-derived TCR with human-derived TCRs and an affinity matured TCR, using in vitro co-culture and in vivo adoptive T cell transfer in tumor-bearing mice. Alanine scan, x-scan, LCL assay were employed to address the cross-reactivity of the NY-ESO-1157-165 specific TCRs. We also used human tissue cDNA library and human primary cells to assess the safety of adoptive T cell therapies targeting NY-ESO-1 antigen in the clinic. One of the murine-derived human TCRs, TCR-ESO, exhibited higher functional avidity compared to human-derived NY-ESO-1157-165 specific TCRs. TCR-ESO appeared to have similar efficiency in antigen recognition as an in vitro affinity-matured TCR, TCR 1G4-α95LY, which was applied in clinical trials. TCR-ESO showed little cross-reactivity, in contrast to TCR 1G4-α95LY. Our data indicate that highly effective TCRs against NY-ESO-1 are likely deleted in humans due to tolerance mechanisms, and that the TCR gene loci transgenic mice represent a reliable source to isolate effective and highly-specific TCRs for adoptive T cell therapies.